30(2x-1)=6(x+4)+3

Simple and best practice solution for 30(2x-1)=6(x+4)+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 30(2x-1)=6(x+4)+3 equation:


Simplifying
30(2x + -1) = 6(x + 4) + 3

Reorder the terms:
30(-1 + 2x) = 6(x + 4) + 3
(-1 * 30 + 2x * 30) = 6(x + 4) + 3
(-30 + 60x) = 6(x + 4) + 3

Reorder the terms:
-30 + 60x = 6(4 + x) + 3
-30 + 60x = (4 * 6 + x * 6) + 3
-30 + 60x = (24 + 6x) + 3

Reorder the terms:
-30 + 60x = 24 + 3 + 6x

Combine like terms: 24 + 3 = 27
-30 + 60x = 27 + 6x

Solving
-30 + 60x = 27 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-30 + 60x + -6x = 27 + 6x + -6x

Combine like terms: 60x + -6x = 54x
-30 + 54x = 27 + 6x + -6x

Combine like terms: 6x + -6x = 0
-30 + 54x = 27 + 0
-30 + 54x = 27

Add '30' to each side of the equation.
-30 + 30 + 54x = 27 + 30

Combine like terms: -30 + 30 = 0
0 + 54x = 27 + 30
54x = 27 + 30

Combine like terms: 27 + 30 = 57
54x = 57

Divide each side by '54'.
x = 1.055555556

Simplifying
x = 1.055555556

See similar equations:

| 7x=x+8x+3 | | 32x+11(5-12x)=21 | | 99=8+7x | | x-4-7=9 | | (y+1)+4= | | t(t+11)=70 | | x_4-7=9 | | 21x-17=193 | | -2c+8=5c-10 | | 3t-7=5-t | | 8h-8=6h+4+2h | | -60-4x=4(1-5x) | | 2a-13=-4a-13 | | (7x-11)+(5x-1)=180 | | x_4-6=9 | | 2(x+4)=-7(x+2/9) | | 12x^2+8x-7= | | b=1.5-2 | | t=(3t)(70m^2) | | 3(f+4)+2f= | | 4y+17.6=10(y-1) | | 4x-5(2x-3)=-15 | | 4a=6 | | 0=6x^2+12x+8 | | 7-5(-3-8n)=-46+6n | | -3-4x+20x^2= | | 8x-4=7x+4 | | 2(x+1)=x-7 | | [x+4]=17 | | M+2M+6M-4= | | 4(2m+5)=7a-3 | | b+11/3= |

Equations solver categories